The Role of Academic‐Language Features for Reading Comprehension of Language‐Minority Students and Students From Low‐SES Families. Issue 1 (11th September 2014) - Heppt, Birgit; Haag, Nicole; Böhme, Katrin; Stanat, Petra
Abstract Academic language is frequently assumed to be especially challenging for students from families of low socioeconomic status (SES) and even more so for language‐minority students. Due to their often especially disadvantaged position regarding socioeconomic background and exposure to the language of instruction, language minority students are considered to suffer from a double disadvantage when processing complex academic language. To test this assumption, the present study investigated the relationships between various academic language features and differential item functioning (DIF) in a reading comprehension test for language‐minority students on the one hand and German monolingual students from low‐SES families on the other hand. The analyses are based on data of 19, 108 fourth‐grade students who took part in the reading comprehension test of the German National Assessment Study in elementary school. Our findings indicate that both lexical and grammatical features of academic language correlate with DIF disfavoring language‐minority students, with especially pronounced effects for long and complex words and average sentence length. For German monolingual students from low‐SES families, fewer features were associated with DIF, and the correlations were generally smaller than for language‐minority students. Findings are discussed in relation to the assumed double disadvantage of language‐minority students in the comprehension of academic language.